Analisis Konsumsi Daging Sapi pada Tingkat Rumah Tangga di Provinsi Aceh - Zulkarnain Zulkarnain; Asmawati Asmawati; Sofyan Sofyan (Jurnal Agrisep, 2017)
This study aimed to analyze the factors which affect the consumption of beef and to determine the income elasticity, price elasticity of beef, cross-price elasticity of demand for beef at the household level in urban and rural locations in the province of Aceh, using data samples Susenas 2015 that consist of 3,308 urban households and 7,102 rural households. The analytical method used was censored regression model using the tools of Eviews 9. The results showed that income, level of education of household head, the price of beef, chicken meat and tetelan significantly affect of meat consumption in urban areas. Chicken meat and tetelan are substitutes to beef. Beef consumption is only affected rural households by income, education of household head and beef prices. Beef is a normal good and elastic. In order to increase the consumption of beef for the people of Aceh, the government is expected to be able to create a policy that can guarantee the availability of beef by increasing the production of beef. And cattle ranchers are expected to support the availability of beef.